Lrrc7 mutant mice model developmental emotional dysregulation that can be alleviated by mGluR5 allosteric modulation - Chong, Chi Ho (Transl Psychiatry, 2019)
LRRC7 has been identified as a candidate gene for severe childhood emotional dysregulation. Direct experimental evidence for a role of LRRC7 in the disease is needed, as is a better understanding of its impact on neuronal structure and signaling, and hence potential treatment targets. Here, we generated and analyzed an Lrrc7 mutant mouse line. Consistent with a critical role of LRRC7 in emotional regulation, mutant mice had inappropriate juvenile aggressive behavior and significant anxiety-like behavior and social dysfunction in adulthood. The pivotal role of mGluR5 signaling was demonstrated by rescue of behavioral defects with augmentation of mGluR5 receptor activity by 3-Cyano-N-(1,3-diphenyl-1H-pyrazol-5-yl)benzamide (CDPPB). Intra-peritoneal injection of CDPPB alleviated abnormal juvenile behavior, as well as anxiety-like behavior and hypersociability at adulthood. Furthermore, mutant primary neurons had impaired neurite outgrowth which was rescued by CDPPB treatment. In conclusion, Lrrc7 mutant mice provide a valuable tool to model childhood emotional dysregulation and persistent mental health comorbidities. Moreover, our data highlight an important role of LRRC7 in mGluR5 signaling, which is a potential new treatment target for anxiety and social dysfunction.